Perancangan Konseptual Desain pada Aplikasi Media Interaktif tentang pengenalan Sistem Ekologi Hewan bagi Siswa/Siswi Sekolah Dasar Negeri 02 Pelita Karya Subang - Rayhan Pratama, Abi; Roedavan, Rickman; Purna Kurniawan, Ady (eProceedings of Applied Science, 2023)
Abstract—Technology can help us in our daily life, there is also support in the field of education. Students at Pelita Karya 02 State Elementary School still find it difficult to understand easily about the ecology of animals or the types of animals especially with the protracted pandemic conditions, therefore, and after the pandemic has begun to subside, teachers also have difficulties in the teaching and learning process due to lack of access and adequate technology so that students at Pelita Karya 02 State Elementary School are not motivated and their learning is hampered. The purpose of making this learning media is to facilitate students and teachers in the learning process and interest in learning[1]. Interactive multimedia learning media is very effective to be used in the learning process especially for students with visual learning styles [2]. The method used in making this application is the Multimedia Development Life Cycle method. The method used in designing and developing a media application which is a combination of image, sound, video and animation media. There are also in this production stage using supporting applications such as Adobe Photoshop, Adobe Illustrator, Adobe Audition, Figma and Unity. By making this interactive media-based educational animal ecology game application, it can provide high interest and interest access to Natural Science learning for students at Pelita Karya 02 State Elementary School Subang. Measurement results from application testing for each aspect are obtained the aspect value of Pragmatic Quality is 1.93, then Hedonic Quality is 2.04 which is also the highest result, the stimulation result is Excellent (verygood). For the average result, all (Overall) get 1.99 with the stimulation which is Excellent (verygood).Kata kunci—game based learning, media interactive, MDLC